Optimalisasi Peran Lembaga Pelatihan Dalam Implementasi Kurikulum Berbasis Cinta Di Madrasah - Lubis, Mohammad Halomoan (JENTRE, 2025)
The launch of the Love-Based Curriculum (Kurikulum Berbasis Cinta/KBC) by Indonesia’s Ministry of Religious Affairs in 2025 represents a transformative innovation in Islamic education. KBC seeks to foster “schools of love” by instilling values of compassion, moderation, and ecological awareness. This study aims to analyze the role of the Ministry’s internal training institutions—the Center for Competency Development (Pusbangkom), Religious Training Centers (BDK), and Religious Training Units (LDK)—in accelerating and sustaining the implementation of KBC. Employing a descriptive qualitative approach, the research combines library study and policy analysis. Data were drawn from official regulations, government documents, and academic literature on curriculum reform, teacher training, and religious moderation. The findings indicate that the Ministry possesses a strong training ecosystem, including institutional networks, professional trainers (Widyaiswara), and digital-based learning facilities. Nevertheless, a key challenge lies in the limited involvement of training institutions during the early planning stages of KBC. The study concludes that comprehensive engagement of these institutions—from planning to implementation and evaluation—is essential. Further research is recommended to conduct empirical case studies in madrasahs to assess the effectiveness of KBC training models.